DOES THE KNOWLEDGE OF PRESENT AND PAST PARTICIPLES PHRASES CORRELATE WITH STUDENTS’ READING COMPREHENSION ACHIEVEMENT? - Ismailia Putri Nor Rachman; Chusnul Chotimah (Lingua, 2018)
This study was conducted with the main aim finding out whether or not there was significant correlation between students’ knowledge of present and past participle phrases and their reading comprehension achievement of descriptive text. It studied two variables: Students’ knowledge of present participle and past participle as Independent Variable, and reading comprehension achievement as Dependent Variable. This research was conducted to the students of grade ten at SMK Global Cendekia, Cakung East Jakarta in the Academic Year of 2017/2018 which consists of 3 classes. The samples were 30 students taken from the total target population of 124 students. The samples were taken through Cluster Random Sampling Technique. The samples were students at class 10 -C. The design used was ex-post-facto design in term of co-relational study. To analyze the data the researcher used the Person Product Moment correlation test that yielded sig, 0,000, which is lower than 0,05 (5%), and rxy = 0,844, which is higher tha the critical value of r-tabel 0,324.